Practicality of a patient self-assessment checklist to manage dementia risk factors in GP practices - Francisca S. Rodriguez; Hanna L. Knecht; Bernhard Michalowsky; Doreen Goerss; Stefan Teipel; Wolfgang Hoffmann; Marina Boccardi (Scientific Reports)
Abstract A screening tool may help determine who in the population is exposed to which dementia risk factor and, in this way, prevent or delay symptoms. With this study, we examined the practically of using a patient self-completion screening checklist for detecting dementia risk factors with general practitioners (GP). The checklist ‘CogFit’ was developed based on systematic reviews and meta-analyses. Fourteen GPs (average age 44.8 years; 71.4% female) tested it with their patients and reported their experiences in a questionnaire and the System Usability Scale (SUS). In our survey, 57.2% of the GPs considered the checklist useful and most GPs (83%) indicated that the current version is sufficient. The user-friendliness of the CogFit checklist was good (SUS score M = 73.13, SD = 10.45). Most GPs (71.4%) reported having gained important information about their patients. 69% gave lifestyle advice and 61.5% referred their patients to brochures or courses. Yet, about two thirds (64.3%) reported an increased workload and four GPs disagreed to use the checklist in future. Our results indicate an overall good practicality of our patient self-completion checklist (CogFit) in primary care. Further research involving patients and estimating the overall effectiveness on cognitive health is needed.